mosGILT antibodies interfere with Plasmodium sporogony in Anopheles gambiae - Brady Dolan; Tomás Correa Gaviria; Yuemei Dong; Peter Cresswell; George Dimopoulos; Yu-Min Chuang; Erol Fikrig (Nature Communications)
Abstract Plasmodium, the causative agents of malaria, are obtained by mosquitoes from an infected human. Following Plasmodium acquisition by Anopheles gambiae, mosquito gamma-interferon-inducible lysosomal thiol reductase (mosGILT) plays a critical role in its subsequent sporogony in the mosquito. A critical location for this development is the midgut, a tissue we show expresses mosGILT. Using membrane-feeding and murine infection models, we demonstrate that antibodies against mosGILT reduce the number of P. falciparum and P. berghei oocysts in the midgut and the infection prevalence of both species in the mosquito. mosGILT antibodies act in the mosquito midgut, specifically impacting the Plasmodium oocyst stage. Targeting mosGILT can therefore interfere with the Plasmodium life cycle in the mosquito and potentially serve as a transmission-blocking vaccine.